Pengaruh Payment Gateway Terhadap Kinerja Keuangan pada UMKM Kota Palembang - Shania Risky Royanti; Fitria Suri (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Financial Technology (Fintech) is the result of a combination of financial services and technology which ultimately changes the business model from conventional to modern. Consumers who initially had to pay face to face and carry a certain amount of cash can now make remote transactions by making payments through the application in just seconds. Mobile phones have helped MSMEs to be more productive and increase their sales thereby improving financial performance. Keywords: Fintech, Financial Performance, Consumers